Biosynthesis of the Sex Pheromone Component (E,Z)-7,9-Dodecadienyl Acetate in the European Grapevine Moth, Lobesia botrana, Involving ∆11 Desaturation and an Elusive ∆7 Desaturase - Ding, Bao-Jian (J Chem Ecol, 2021)
The European grapevine moth, Lobesia botrana, uses (E,Z)-7,9-dodecadienyl acetate as its major sex pheromone component. Through in vivo labeling experiments we demonstrated that the doubly unsaturated pheromone component is produced by ∆11 desaturation of tetradecanoic acid, followed by chain shortening of (Z)-11-tetradecenoic acid to (Z)-9-dodecenoic acid, and subsequently introduction of the second double bond by an unknown ∆7 desaturase, before final reduction and acetylation. By sequencing and analyzing the transcriptome of female pheromone glands of L. botrana, we obtained 41 candidate genes that may be involved in sex pheromone production, including the genes encoding 17 fatty acyl desaturases, 13 fatty acyl reductases, 1 fatty acid synthase, 3 acyl-CoA oxidases, 1 acetyl-CoA carboxylase, 4 fatty acid transport proteins and 2 acyl-CoA binding proteins. A functional assay of desaturase and acyl-CoA oxidase gene candidates in yeast and insect cell (Sf9) heterologous expression systems revealed that Lbo_PPTQ encodes a ∆11 desaturase producing (Z)-11-tetradecenoic acid from tetradecanoic acid. Further, Lbo_31670 and Lbo_49602 encode two acyl-CoA oxidases that may produce (Z)-9-dodecenoic acid by chain shortening (Z)-11-tetradecenoic acid. The gene encoding the enzyme introducing the E7 double bond into (Z)-9-dodecenoic acid remains elusive even though we assayed 17 candidate desaturases in the two heterologous systems. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10886-021-01252-3.